Academic dependency in the social sciences structural reality and intellectual challenges - Sinha-Kerkhoff, Kathinka; Alatas, Farid Syed.; SEPHIS (Programme : Netherlands).; Asian Development Research Institute (Patna, India). (New Delhi Manohar, 2010)
Papers presented at an international conference at Patna in 2008.
"SEPHIS; Asian Development Research Institute."
Keywords: Social sciences -- Study and teaching -- Developing countries -- Congresses; Educational psychology -- Developing countries -- Congresses